Complex transmission epidemiology of neglected Australian arboviruses: diverse non-human vertebrate hosts and competent arthropod invertebrate vectors - Taylor-Robinson, Andrew W. (Frontiers in Microbiology, 2024)
More than 75 arboviruses are indigenous to Australia, of which at least 13 are known to cause disease in humans. Alphaviruses are the most common arboviruses, notably including Ross River and Barmah Forest viruses, which contribute a significant public health and economic burden in Australia. Both can cause febrile illness with arthritic symptoms. Each circulates nationally across diverse climates and environments, and has multi-host, multi-vector dynamics. Several medically important flaviviruses also circulate in Australia. Infection with Murray Valley encephalitis or Kunjin viruses is less common but is associated with brain inflammation. Key research priorities for Australian arboviruses aim to understand clinical manifestations, develop timely diagnostics, and identify transmission cycles that permit the maintenance of arboviruses. While these can now be answered for a handful of notifiable alphaand flaviviruses there are others for which non-human vertebrate hosts and competent arthropod invertebrate vectors are still to be identified and/or whose role in transmission is not well understood. One or more of these 'neglected' arboviruses may be the causative agent of a proportion of the many thousands of fever-related illnesses reported annually in Australia that at present remain undiagnosed. Here, what is known about enzootic cycling of viruses between arthropod vectors and mammalian and avian reservoir hosts is summarised. How and to what extent these interactions influence the epidemiology of arbovirus transmission and infection is discussed.